SWOT and AHP Analysis in Marketing Strategy at Hotel Baby Angel Dieng, Red Doorz Partner - Nailil Mahfiroh; M. Trihudiyatmanto; Eni Candra Nurhayati (UP2MF Fakultas Ekonomi dan Bisnis, Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2025)
Purpose - This study aims to analyze marketing strategies to improve the marketing of the Baby Angel Dieng Mitra Red Doorz Hotel in Wonosobo, Central Java. Methodology - This study employed a qualitative approach. First, a SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis, an Internal Factors Analysis Summary (IFAS), an External Factors Analysis Summary (EFAS), and an Analytic Hierarchy Process (AHP) analysis were used. The SWOT analysis was used to identify internal and external factors influencing the Baby Angel Dieng Mitra Red Doorz Hotel. The IFAS and EFAS were used to weight and rank these factors to determine the hotel's position within the SWOT matrix. The AHP method was then used to prioritize optimal marketing strategies. Fundings - This study indicates that the Baby Angel Dieng Mitra Red Doorz Hotel's SWOT analysis falls within quadrant I, which supports an aggressive strategy. Recommended strategies include more extensive promotions and improving the hotel's quality by increasing collaboration with third parties. Meanwhile, the AHP analysis identified that the first priority marketing strategy is strategy 5, namely by adding facilities and employees and holding training and education programs for employees. Limitations - This study has several limitations, such as not obtaining all internal data, and the rapid development of social media and technology may make the analysis less accurate due to future changes. Implications - The results of this study aim to address the issue of unmet marketing targets at Hotel Baby Angel Dieng Mitra Red Doorz and serve as input and reference material for investors considering investing in Hotel Baby Angel Dieng Mitra Red Doorz.